Linear matrix inequality-based model matching H2 output feedback control of a new leak tightness machine working based on hydrostatic pressure aging method - Yalcin, Baris Can; Koyun, Ahmet (SAGE PUBLICATIONS LTD, 2018)
Fluid leaks owing to broken pipes can be a serious problem for any hydraulic system. The main reasons for pipe breakage are spontaneously changing hydrostatic and hydrodynamic pressure values inside the pipe or faults occurring during the pipe manufacturing process. Therefore, different kinds of leak tightness tests are required in many standards for approval of the pipes used in both academic researches and industrial applications. Hydrostatic pressure aging is the most common method among leak tightness test procedures. However, conventional test machines cannot reach above 700 bar owing to their mechanical specifications. In this study, the design of a new leak tightness test machine that can reach above 1200 bar and its Linear matrix inequality-based model matching H-2 output feedback control have been achieved. The efficacy of the test machine and proposed controller have been shown with both simulation and experimental results.
Keywords: Linear matrix inequality; model matching; H-2 output feedback; linear systems; hydrostatic pressure aging; impedance control; DISCRETE-TIME-SYSTEMS; CYLINDRICAL-SHELLS; STABILIZATION; STABILITY; PIPES; DESIGN; Automation & Control Systems; Instruments & Instrumentation